Competition in World Politics Knowledge, Strategies and Institutions - Russ, Daniela; Stafford, James (Global Studies, 2021)
The »return of great power competition« between (among others) the US, China, Russia and the EU is a major topic in contemporary public debate. But why do we think of world politics in terms of »competition«? Which information and which rules enable states and other actors in world politics to »compete« with one another? Which competitive strategies do they pursue in the complex environment of modern world politics? This cutting-edge edited collection discusses these questions from a unique interdisciplinary perspective. It offers a fresh account of competition in world politics, looking beyond its military dimensions to questions of economics, technology and prestige.